Analysis of the relation between change perception and demographic factors (A research in Turkish hospital sector) - (:unkn) unknown (Common Ground Publishing, 2010)
Today change has become an integral part of our lives. Not only countries or enterprises but also individuals must change and improve themselves in line with the changing environmental conditions. In this study, today's one of the most important issues; the concept of 'change' is addressed in terms of business and management and the way how employees perceive the concept of change and the demographic factors that effect this change such as gender, age, marital status were analyzed to detect if they have any effect on the perception of change. This study not only keeps the light for the institution it has held but also it is crucial for other institutions change. Especially in the hospital industry where knowledge workers are in charge, it is difficult to make change. For the study, a public hospital that is charged for the program called 'Health Transformation in Turkey' has been chosen. This work was carried out a week before the program started the planned change. Research was distributed to the administrators, doctors, nurses and other staff of 415 people in total, who work at the hospital. However, the number of responding to the survey is 227. In the study, to determine the perception of individual's perception of change 'an organizational change perception scale' that asks questions in order to define the features of individuals such as gender, position, educational status and position has been used. The scales have been analyzed by SPSS 11.5. After the validity and reliability analysis of the change perception scale is finished, the relation between change and demographic characteristics has been examined one by one. When the relationship between marital status and organizational change was analyzed, it is stated that the married individuals perceive change more affirmative according to single individuals. According to the status and the results of organizational change perception of the participants, it is detected that there is meaningful relationship between the status and the organizational change perception factor. It is also found out that especially nurses and administrators have more positive thoughts than doctors in change perception. By the guidance this analysis, according to the research results it can be specified that there is significant relationship between demographic characteristics of individuals and perception of change. However, it can be also seen in our study, these results change from business to business, institution to institution or even from industry to industry. Therefore, every business that decided to change should assess the previous works done in this field. In addition, they should not forget that different results from the previous works may arise in their business. For this reason, before starting this change study at work, every manager should determine his employees' perception of organizational change and they should also detect the characteristics of the employees' that affect the perception of change and take appropriate precautions. This is vital in terms of reducing negativities that may occur during change process. © Common Ground.
Keywords: Business; Change; Change management; Change perception; Employee